POTENSI PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PERSONAL HYGIENE MENSTRUASI - Komariyah, Lailatul; Mukhoirotin, Mukhoirotin (Universitas Pesantren Tinggi Darul Ulum, 2018)
Hygiene at the time of menstruation is important in determining the health of reproductive organs. If not kept clean, it will cause microorganisms such as bacteria, fungi and viruses that can interfere with the function of reproductive organs. This study aims to determine the effect of health education on personal knowledge of menstrual hygiene. The design in this research is quasi experimental with pretest posttest control group design. The population in this study were 171 respondents and 108 respondents, using simple random sampling technique. The independent variables of this research are health education and dependent variables are personal hygiene knowledge. The research instrument using questioner, the data were analyzed using Wilcoxon and Mann Whitney test with ? ? 0,05. Wilcoxon test result in treatment group was p = 0.000 and control group p = 0,083. Mann Whitney test results obtained p = 0,000 (p <?). The results of this study indicate that there is an effect of health education on personal knowledge of menstrual hygiene and there is a significant difference in personal knowledge of menstrual hygiene in the treatment group and control group. Effective health education increases personal knowledge of Menstrual Hygiene.Keywords : Health Education, Knowledge, Personal Hygiene, Menstruation